2008
DOI: 10.1001/archsurg.143.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Carcinoid Tumors

Abstract: Main Outcome Measure: Margin status of tumor resection. Results: Eighty-five patients were identified (median age at diagnosis, 55 years). Thirty-three tumors (39%) were asymptomatic and diagnosed during screening colonoscopy. Eleven tumors (13%) were metastatic at presentation. Of the 85 tumors, 48 (56%) were smaller than 1.0 cm. Endoscopic therapy was performed in 46 patients (54%). Of these, 38 patients (83%) had tumors with positive or indeterminate margins on histologic examination; of whom 6 (16%) had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 13 publications
4
37
0
Order By: Relevance
“…About 80% of typical rectal carcinoid cases are 10 mm or less in size, restricted in submucosal layer with less metastasis, contributing to its favorable prognosis with 5-year survival rate estimated around 88.3% 7. For this reason, local treatment with endoscopic resection or minimal invasive surgery, rather than radical resection, is preferred in many cases 8,9,22,25-28. Rectal carcinoid of 10 mm or less in size, without lymphovascular, proper muscle invasion or lymph node metastasis, is reported to have good prognosis of around 98.9% to 100% of 5-year survival rate 6,21,22,29…”
Section: Discussionmentioning
confidence: 99%
“…About 80% of typical rectal carcinoid cases are 10 mm or less in size, restricted in submucosal layer with less metastasis, contributing to its favorable prognosis with 5-year survival rate estimated around 88.3% 7. For this reason, local treatment with endoscopic resection or minimal invasive surgery, rather than radical resection, is preferred in many cases 8,9,22,25-28. Rectal carcinoid of 10 mm or less in size, without lymphovascular, proper muscle invasion or lymph node metastasis, is reported to have good prognosis of around 98.9% to 100% of 5-year survival rate 6,21,22,29…”
Section: Discussionmentioning
confidence: 99%
“…This finding coincides with multiple previous studies which have reported no recurrences after resection of tumors ≤1.0 cm, over a median follow-up period of up to 6.4 years and a cohort as large as 84 patients [1315]. Alternatively, Kwaan et al reported 2 of 48 patients (4%) with a rectal carcinoid tumor <1.0 cm had distant metastatic recurrence discovered at 5 and 13 years after resection [12]. The initial management and follow-up surveillance of these 2 patients is unclear.…”
Section: Resultssupporting
confidence: 91%
“…The primary tumor had been small and confined to the submucosa without any evidence of vascular involvement; recurrence of such a tumor with a long interval from curative surgery is quite rare (10,11). A case of liver metastasis 13 years after resecting a rectal NET smaller than 10 mm has been reported (12). Our case shows a longer time period from the primary operation to recurrence.…”
Section: Discussionmentioning
confidence: 99%